METHOD OF CALCULATION OF EVAPOTRANSPIRATION AND REGULARITIES OF SPATIO-TEMPORAL CHANGES IN LAKE SEVAN BASIN (Proceedings of the YSU C: Geological and Geographical Sciences, 2009)
Using data from GGI-3000 evaporators, multifactor correlations between evaporation in the Lake Sevan basin and the actual (observed) values of meteorological elements for 1960–2000 that determine it were studied and analyzed. Reliable calculated equations of evapotranspiration has been got. The map of evapotranspiration values in Lake Sevan basin for July–August period is made up. Regularities of spatial distribution of evapotranspiration are exposed.
Keywords: Lake Sevan basin; GGI-3000; evaporation; evapotranspiration; multifactor correlations